Dampak Pengumuman Struktur Danatara terhadap Volatilitas Saham Perusahaan Bank BUMN: Event Study - Maulana, Rahman; Hanifani, Nida (Penerbit Goodwood, 2025)
Purpose: This study examines the impact of Danantara structure announcements on stock volatility of state-owned banking companies listed on the Indonesia Stock Exchange, focusing on market reactions and efficiency characteristics. Methodology/approach: The Event Study methodology is employed to analyze four state-owned banks (BBRI, BMRI, BBNI, and BBTN) using a six-day event window during March 2025. Abnormal Return (AR) and Cumulative Average Abnormal Return (CAAR) are calculated using a market-adjusted return approach. Results/findings: The Danantara structure announcement affects stock volatility with varying market reactions. Positive reactions occurred on the first day after the announcement, followed by significant market corrections in subsequent days. Statistical tests show no significant difference between pre- and post-announcement periods. Conclusions: The findings indicate that the Indonesian capital market exhibits semi-strong efficiency characteristics with overreaction and correction patterns, consistent with emerging market behavior. Limitations: The study is limited to four state-owned banks, a six-day event window, and a single event period in March 2025, which may not fully capture long-term or cross-industry effects. Contribution: This research contributes to behavioral finance and emerging market literature by documenting investor overreaction patterns in Indonesian capital markets. For policymakers, it provides insights on the impact of government announcements on market stability. For investors and fund managers, it offers evidence for better decision-making in response to structural changes. For the banking industry, it informs corporate communication strategies regarding institutional restructuring announcements.